Historians, Computing and the World-Wide-Web. - Turnbull, Paul (Australian Historical Studies, 2010)
This article provides a brief overview of historians' engagement with computing and information communication technologies since the creation of the World-Wide-Web in the early 1990s. It considers the failure of historical computing since the mid-1970s to interest the wider profession, and what this has meant for historians drawn to explore the potential of hypertext and the Web for history teaching and research over the past fifteen years. The article argues that given the ubiquity of Web-based communication, there is much to be gained by the historical profession taking a more supportive approach to the use of digital technologies.